Hydrodynamic analysis of noise propagation by the high skew marine propeller working in non-uniform inflow - Hadipour, Ali; Khanzadi, H.; Abadi, K.A.V.; Motahari, H. (Zielona Góra: Uniwersytet Zielonogórski)
Being able to predict ship and marine propulsion noise is an important issue for naval architectures and the international maritime community. The main objective of this paper is the numerical investigation on the noise propagation by the high skew marine propeller working in a non-uniform inflow via RANS solver in the broadband frequency range.
Keywords: noise; high skew marine propeller; pressure fluctuating; blade passing frequency